Book review: this is me! whatever you say - Wajdi, Majid; Pratiwi, Ni Kadek Anjelia Putri; Putra, I Komang Agus Januarta Sutisma; Amanah, Firda Maulia; Muhamadias, Nusrat; Amandari, Ni Kadek Pande Anggi (Yayasan Mitra Persada Nusantara, 2023)
The purpose of writing is to convey to readers whether a book or work deserves a response from the public or not. Besides that, it is also to give considerations to other works of art such as plays, films, and a performance. Because the considerations conveyed by reviewers must be adjusted to the tastes of readers, a review published in a magazine may not be the same. The method we use in reviewing a book entitled